2023
DOI: 10.1021/acs.orglett.3c02958
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Noremestrin with a Sulfur-Bearing 15-Membered Macrocyclic Lactone from Emericella sp. 1454

Yuchuan Chen,
Tongmei Xiao,
Shuyue Guo
et al.

Abstract: Two previous unreported epipolythiodioxopiperazines of the emestrin family, namely, noremestrin A (1) and secoemestrin E (2), were successfully isolated from the fungal source Emericella sp. 1454. Employing comprehensive spectroscopic techniques, such as high-resolution electrospray ionization mass spectrometry, infrared, and nuclear magnetic resonance (NMR), along with NMR and electronic circular dichroism calculations, the chemical structures of compounds 1 and 2 were elucidated. Particularly noteworthy is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The MS data showed that there was [M + H] + ion at m/z 253.0894. The 13 C NMR, 1 H NMR, homonuclrar correlation spectroscopy (COSY), nuclear overhauser effect spectroscopy (NOESY),heteronuclear single‐quantum correlation (HSQC) and heteronuclear multiple‐bond correlation (HMBC) 34 of the blue fluorescent substance are shown in Figs 6–11, respectively, and the obtained data are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The MS data showed that there was [M + H] + ion at m/z 253.0894. The 13 C NMR, 1 H NMR, homonuclrar correlation spectroscopy (COSY), nuclear overhauser effect spectroscopy (NOESY),heteronuclear single‐quantum correlation (HSQC) and heteronuclear multiple‐bond correlation (HMBC) 34 of the blue fluorescent substance are shown in Figs 6–11, respectively, and the obtained data are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…1454, has an unusual sulfur-bearing 15-membered macrocylic lactone. 8 The structure of asperinamide A 8 , from Aspergillus sp. TE-65L, was confirmed by X-ray analysis.…”
mentioning
confidence: 99%